Obstacles to the application of the concept of quality management in higher institutes Field Study (Al-Farooq Journal of Sciences, 2026)
This research aims to identify the most important obstacles to the application of the concept of quality management in higher institutes, from the point of view of employees, and to identify the most important principles and components that must be adopted by technical education institutions in order to apply the concept of quality management efficiently and effectively, and to clarify the effective and positive role of the concept of quality management in improving the level of higher institutes, and the importance of its application. The analysis was processed using the statistical program (SPSS), and the researcher reached a number of results, the most important of which are the following:1)  The most prominent obstacles facing the application of the concept of quality management in higher institutes is the lack of attention to modern educational aspects, which is one of the most important obstacles to the application of the concept of quality management in higher institutes.2) The lack of interest of higher institutes in scientific research, which represents the basis for improving the level and degree of ranking of higher education institutions in the global assessment, which can only be improved through the application of the philosophy of the concept of quality management and the achievement of its goals and advantages.3)The weak conviction of the administrative and academic leaders in the higher institutes in the concept of quality management, due to their lack of awareness of the concept and its importance in improving the level of services provided and its impact on the country.4)The most important obstacles in the application of the concept of quality management in higher institutes are in the educational aspects, scientific research aspects, social responsibility, leadership aspects, and organizational aspects are arranged respectively and with high negative percentages, and do not support the application of the concept in a positive way.5) The existence of many obstacles faced by higher institutes in the application of the concept of quality management and the inability to address and exceed them does not enable them to achieve the benefits and objectives of total quality management, and thus the inability to improve and develop the level of quality of educational services provided.
Keywords: Obstacles – Quality – Higher Institutes – Management – Employees